Educational Narratives of a Media-Supported ASSURE–SPUR Design for Systematic and Multidimensional Fraction Learning in Grade V Elementary School - Taopik Rahman; Muhammad Rijal Wahid Muharram; Nasser Qudah (Yayasan Adra Karima Hubbi, 2026)
Background. Fraction learning in elementary school often remains centred on computational procedures, while conceptual understanding, real-world use, and visual representation receive less systematic attention. Purpose. This study aimed to develop and evaluate a media-supported ASSURE–SPUR learning design for fraction multiplication in Grade V elementary school. Method. The study used a design-based research approach consisting of needs analysis, design planning, expert validation, limited classroom implementation, revision, and evaluation. Data were collected through teacher interviews, curriculum document analysis, expert validation sheets, classroom observations, student worksheets, student and teacher response questionnaires, and analysis of students’ work. Results. The needs analysis showed that students could often follow computational steps but struggled to explain the meaning of fraction operations, connect symbolic forms with visual models, and apply fractions in contextual situations. The developed design integrated the instructional stages of ASSURE with the SPUR dimensions of mathematical understanding: Skills, Properties, Uses, and Representations. The learning tools included lesson plans, student worksheets, contextual videos accessed through QR codes, Mathigon, Quizizz, manual representations, and SPUR-based tasks. Expert validation produced an average score of 4.46 out of 5, indicating that the design was highly valid. Conclusion. The media-supported ASSURE–SPUR design is feasible, preliminarily practical, and pedagogically promising for supporting more systematic and multidimensional fraction learning.